Inhibition of the Akt/NF-κB pathway is involved in the anti-gastritis effects of an ethanolic extract of the rhizome of Atractylodes macrocephala. (15th July 2022) - Amin, Aftab; Hossen, Muhammad Jahangir; Fu, Xiu-Qiong; Chou, Ji-Yao; Wu, Jia-Ying; Wang, Xiao-Qi; Chen, Ying-Jie; Wu, Ying; Yin, Cheng-Le; Dou, Xiao-Bing; Liang, Chun; Chou, Gui-Xin; et al.
Abstract: Ethnopharmacological relevance: Gastritis can lead to ulcers and the development of gastric cancer. The rhizome of Atractylodes macrocephala Koidz. (Asteraceae), a traditional Chinese medicinal herb, is prescribed for the treatment of gastric disorders, hepatitis and rheumatism. Its bio-active compounds are considered to be particularly effective in this regard. However, the molecular processes of the herb's anti-inflammatory activity remain obscure. This study elucidates a mechanism upon which an ethanolic extract of this herb (Am-EE) exerts anti-inflammation effects in RAW264.7 macrophage cells (RAW cells) stimulated by lipopolysaccharide (LPS) treatment and HCl Ethanol-stimulated gastritis rats. Aim of the study: To investigate the anti-gastritis activities of Am-EE and explore the mode of action. Materials and methods: Ethanol (95%) was used to prepare Am-EE. The quality of the extract was monitored by HPLC analysis. The in vivo effects of this extract were examined in an HCl Ethanol-stimulated gastritis rat model, while LPS-stimulated RAW cells were used for in vitro assays. Cell viability and nitric oxide (NO) production were observed by MTT and Griess assays. Real-time PCR was used to examine mRNA expression. The PGE2 ELISA kit was employed to detect prostaglandin E2 (PGE2 ). Enzyme activities and protein contents were examined by immunoblotting. Luciferase reporter gene assays (LRA) were employed to observe nuclear transcription factor (NF)-κB activity. The SPSS (SPSS Inc., Chicago, Illinois, United States) application was used for statistical examination. Results: HPLC analysis indicates that Am-EE contains atractylenolide-1 (AT-1, 1.33%, w/w) and atractylenolide-2 (AT-2, 1.25%, w/w) (Additional Figure. A1). Gastric tissue damage (induced by HCl Ethanol) was significantly decreased in SD rats following intra-gastric application of 35 mg/kg Am-EE. Indistinguishable to the anti-inflammation effects of 35 mg/kg ranitidine (gastric medication). Am-EE treatment also reduced LPS-mediated nitric oxide (NO) and prostaglandin E2 (PGE2 ) production. The mRNA and protein synthesis of inducible cyclooxygenase (COX)-2 and NO synthase (iNOS) was down-regulated following treatment in RAW cells. Am-EE decreased NF-κB (p50) nuclear protein levels and inhibited NF-κB-stimulated LRA activity in RAW cells. Lastly, Am-EE decreased the up-regulated levels of phosphorylated IκBα and Akt proteins in rat stomach lysates and in LPS challenged RAW cell samples. Conclusion: Our study illustrates that Am-EE suppresses the Akt/IκBα/NF-κB pathway and exerts an anti-inflammatory effect. These novel conclusions provide a pharmacological basis for the clinical use of the A. macrocephala rhizome in the treatment and prevention of gastritis and gastric cancer. Graphical abstract: Image 1